2018
DOI: 10.3390/polym10040446
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Filler Dispersion in Elastomers: Relating Filler Morphology to Interface Free Energies via SAXS and TEM Simulation Studies

Abstract: The properties of rubber are strongly influenced by the distribution of filler within the polymer matrix. Here, we introduce a Monte Carlo-based morphology generator. The basic elements of our model are cubic cells, which, in the current version, can be either silica filler particles or rubber volume elements in adjustable proportion. The model allows the assignment of surface free energies to the particles according to whether a surface represents, for instance, ‘naked’ silica or silanised silica. The amount … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
(61 reference statements)
1
20
0
Order By: Relevance
“…TEM is frequently used to study filler dispersion in polymer matrices [ 80 ]. Figure 4 shows TEM images of the three types of carbon-based nanofillers in SR matrix, where the grey dots indicate the filler particles.…”
Section: Processing Of Sr/carbon-nanofiller-based Nanocompositesmentioning
confidence: 99%
“…TEM is frequently used to study filler dispersion in polymer matrices [ 80 ]. Figure 4 shows TEM images of the three types of carbon-based nanofillers in SR matrix, where the grey dots indicate the filler particles.…”
Section: Processing Of Sr/carbon-nanofiller-based Nanocompositesmentioning
confidence: 99%
“…Quantities like the strain amplification factor, D=d, the exponents y and Y or the strain heterogeneity parameter s are likely to be dependent on the rubber processing and not just on the system composition. Current work focusses on the development of a morphology generator, which, based on experimental interface tensions, generates close to realistic filler network structures (see for instance references (34,35).). The next step should be the transfer of these static structures to a dynamical model (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…An explanation for this smaller size could be that the peptide cross-linkers restrict chain flexibility, keeping the polymer chains tightly connected. 56 Enzyme-triggered nanogel degradation MMP-triggered nanogel disassembly was analysed using MMP-7 as a model MMP. We first confirmed that the free peptide in solution can be cleaved by MMP-7 as shown using LC-MS (Fig.…”
Section: Nanogel Cross-linking Via Peptides To Increase Stability Andmentioning
confidence: 99%